A promiscuous beta-glucosidase is involved in benzoxazinoid deglycosylation in Lamium galeobdolon. (December 2018) - Hannemann, Laura; Lucaciu, Calin Rares; Sharma, Sapna; Rattei, Thomas; Mayer, Klaus F.X.; Gierl, Alfons; Frey, Monika
Abstract: In the plant kingdom beta-glucosidases (BGLUs) of the glycosidase hydrolase family 1 have essential function in primary metabolism and are particularly employed in secondary metabolism. They are essential for activation in two-component defence systems based on stabilisation of reactive compounds by glycosylation. Based on de novo assembly we isolated and functionally characterised BGLUs expressed in leaves of Lamium galeobdolon ( Lg GLUs). Lg GLU1 could be assigned to hydrolysis of the benzoxazinoid GDIBOA (2, 4-dihydroxy-1, 4-benzoxazin-3-one glucoside). Within the Lamiaceae L. galeobdolon is distinguished by the presence GDIBOA in addition to the more common iridoid harpagide. Although Lg GLU1 proved to be promiscuous with respect to accepted substrates, harpagide hydrolysis was not detected. Benzoxazinoids are characteristic defence compounds of the Poales but are also found in some unrelated dicots. The benzoxazinoid specific BGLUs have recently been identified for the grasses maize, wheat, rye and the Ranunculaceae Consolida orientalis. All enzymes share a general substrate ambiguity but differ in detailed substrate pattern. The isolation of the second dicot GDIBOA glucosidase LgGLU1 allowed it to analyse the phylogenetic relation of the distinct BGLUs also within dicots. The data revealed long periods of independent sequence evolution before speciation. Graphical abstract: Image 1 Highlights: Monocot and dicot DIBOA beta-glucosidases (BGLUs) are promiscuous enzymes. The respective BGLUs of Lamium galeobdolon and Consolida orientalis show convergent evolution. The data set for dicot genes indicates repeated evolution of the specialised metabolite pathway.